Gambaran Hasil X-Ray Thorax Posterior Anterior Pada Pasien Pre Operasi Dengan General Anestesi di RSUD dr. R.Goeteng Taroenadibrata Purbalingga - Sapitri, Novi; Suandika, Made (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Background : Surgery is akk treatment prosedures that use invasive techniques by opening or displaying body parts, and are generally carried out by making an incisionin the part of the body that will be treated until repair is carried out and ending with closing or suturing the wound.The anesthesiologist researches the reading of thorax X-ray results, especially in general anesthesia patients because X-ray are one of the important indicator for anesthesia, especially general anesthesia, anticipation and so that or does not have abnormalities in the lungs, whether there is cardiomyolysis or not, so the anesthesiologist can be preventive fpr the preparation of drugs or the way of anesthesia techniques.objective: To find out the overview of the result of thorax Posterior Anterior X-ray in preoperative patients with General Anesthesia based on age gender, smoking history and length of surgery in preoperative patients. Method : this study uses a quantitative descriptive method with a retrospective approach carried out only to observe and describe a variable and then examine and explain an event with numerical data without testing a certain hypothesis and measurement is carried out 1 time at a certain time. Results : normal posterior anterior (PA) x-ray results were 42 respondents (52.5%), with bronchitis 24 respondents (30.0%), for pneumonia there were 9 respondents (11.3%), while cardiomegaly there were 4 respondents (5.0%) and respondents with pneumothorax results there were 1 respondent (1.3%). Results: normal posterior anterior (PA) x-ray results were 42 respondents (52.5%), with bronchitis 24 respondents (30.0%), for pneumonia there were 9 respondents (11.3%), while cardiomegaly there were 4 respondents (5.0%) and respondents with pneumothorax results there were 1 respondent (1.3%). Conclusion : Based on the study, patients with actions in seeing the results of the PA thorax picture are one of the important indicators for anesthesia, especially in general anesthesia patients.